Memahami Perbedaan Mata Uang (Currency) Dengan Uang (Money) Dalam Investasi Era Modern Perspektif Studi Islam - Saiddaeni (Literasi : Jurnal Kajian Keislaman Multi-Perspektif, 2022)
In this modern era, many people still don't understand the basic difference between currency and money. This mistake often causes them not to realize the existence of inflation and its impact on investing. This lack of understanding can have detrimental effects on both individuals and society. This article is here with the aim of providing information to readers so they can understand the essential differences between currency and money. The method in this article uses a literature study to analyze the difference between currency and money in an investment context. This approach aims to provide a comprehensive understanding of the essential differences between the two concepts, so that readers can find the right investment instrument according to their needs. This research also involves studies of hadith and the Koran. Comparisons between Islamic teachings and modern economics regarding investment will be made to obtain a comprehensive and holistic understanding. The results obtained show that the use of gold and silver as transaction and investment instruments has an important role. Because the currency (fiat) used in the modern era has significant weaknesses, such as inflation which can harm investment value. Islam encourages its people to use gold and silver as a transaction and investment tool that is stable and avoids inflation.